2013
DOI: 10.1007/s00374-013-0841-3
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic N nutrition, C assimilation, and plant water use efficiency in Bambara groundnut (Vigna subterranea L. Verdc) grown in farmers’ fields in South Africa, measured using 15N and 13C natural abundance

Abstract: Bambara groundnut (Vigna subterranea L. Verdc) is the second most important indigenous food legume in Africa. The aim of this study was to evaluate plant growth, N 2 fixation, N contribution, C accumulation, and plant water relations of Bambara groundnut grown in 26 farmers' fields in Mpumalanga Province of South Africa. The data revealed marked (p ≤0.05) differences in plant dry matter (DM) yield, N concentration and content, δ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 39 publications
(41 reference statements)
6
50
4
1
Order By: Relevance
“…The desirable agronomic traits of Bambara groundnut such as yield potential (Berchie et al 2010;BAMFOOD 2012), nutritional composition (Brough and Azam-Ali 1992;Brough et al 1993) drought tolerance and adaptations to marginal soils (Collinson et al 1996;Mwale et al 2007a, b), N-fixation and soil fertility improvement (Kishinevsky et al 1996;Dakora 1998;Herridge and Rose 2000;Herridge et al 2008;Mohale et al 2013) have been documented. The crop largely exists as landraces with few varieties developed through controlled breeding (Massawe et al 2002;Basu et al 2007b;Massawe et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The desirable agronomic traits of Bambara groundnut such as yield potential (Berchie et al 2010;BAMFOOD 2012), nutritional composition (Brough and Azam-Ali 1992;Brough et al 1993) drought tolerance and adaptations to marginal soils (Collinson et al 1996;Mwale et al 2007a, b), N-fixation and soil fertility improvement (Kishinevsky et al 1996;Dakora 1998;Herridge and Rose 2000;Herridge et al 2008;Mohale et al 2013) have been documented. The crop largely exists as landraces with few varieties developed through controlled breeding (Massawe et al 2002;Basu et al 2007b;Massawe et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It could also mean that though the rhizobacteria were available in the soil they might not be nitrogen fixers. Nitrogen available in the soil can also be low if plant density is low since both are positively correlated and might not be as a result of poor symbiotic relationship [30]. This was contrary to other findings which observed that nitrogen increased with increase in microbial population and activities [31].…”
Section: Discussionmentioning
confidence: 68%
“…Phosphate solubilization is a complex phenomenon and it helps to discriminatively screen the bacteria which are able to break down tricalcium phosphate (TCP) and thereby release inorganic phosphate. subtilis [30]. The ability of these isolates to be able to inhibit and/or suppress the growth of both fungi and bacteria implies the richness of the bambara groundnut rhizosphere and its ability to resist diseases and pests.…”
Section: Discussionmentioning
confidence: 99%
“…N fixation was measured using 15 N natural abundance (NA) procedure as suggested by Mohale et al (2014). The 15 N NA of the whole plant (grain plus stover) was measured using the method of Unkovich et al (2008) The % ndfa was calculated using the method reported by Musa et al (2016).…”
Section: Data Collectionmentioning
confidence: 99%